Limits and potential of the use of vouchers for personal services. An evaluation of titres-services in Belgium and the CESU in France - Sansoni, Anna Maria (Brussels, 2009)
"This working paper presents how 'personal services' i.e. labour supplied within the home or the immediate environment of private individuals have developed in France and Belgium via a voucher system. The paper suggests large numbers of regular jobs have been created despite the fact that shorter working hours are a prevalent feature of these new jobs. In comparison with the actual creation of regular jobs, the quality of the jobs in question seems to be definitely more controversial. "